Meubobo Alang: The Sunat Rasul Tradition of the Kluet Tribe in South Aceh - Hasbaini Ben; Dina Miftahul Jannah; Sepri Kurniadi; Anhar Anhar; Muhibuddin Muhibuddin (International Journal of Multidisciplinary Sciences and Arts, 2025)
ABSTRACT The Meubobo alang tradition is a form of intangible cultural heritage that is still preserved by the Kluet community in South Aceh. This ritual is an important part of the Sunat rasul (Prophetic Circumcision) procession. In this ritual, the boy to be circumcised is paraded using an alang (a sedan chair or litter adorned with traditional ornaments), accompanied by prayers and various symbols of respect. This study was aimed to be uncovered the cultural meaning, historical background, and social function of the Meubobo alang tradition within the life structure of the Kluet community. Using a qualitative approach with an ethnographic method, data was collected through direct field observation, in-depth interviews with customary figures and families who practice the tradition, as well as the review of cultural documents. The research findings indicate that Meubobo alang does not only serve as a series of ceremonial activities but also contains spiritual, symbolic, and social values deeply rooted in the local culture. This tradition plays a role in maintaining harmonious family relations, reinforcing ethnic identity, and serving as a medium for transmitting moral values and character to the younger generation. Amidst the current of change and the influence of modernization, Meubobo alang maintains an important position as a form of local wisdom preservation that unites customary values with the principles of Islamic teachings. Thus, this tradition not only reflects cultural continuity but also demonstrates the Kluet community’s ability to preserve their identity and ancestral values.